2014
DOI: 10.1364/boe.5.000961
|View full text |Cite
|
Sign up to set email alerts
|

In vivo adaptive optics microvascular imaging in diabetic patients without clinically severe diabetic retinopathy

Abstract: Abstract:We used a confocal adaptive optics scanning laser ophthalmoscope (AOSLO) to image the retina of subjects with nonproliferative diabetic retinopathy (NPDR). To improve visualization of different retinal features, the size and alignment of the confocal aperture were varied. The inner retinal layers contained clearly visualized retinal vessels. In diabetic subjects there was extensive capillary remodeling despite the subjects having only mild or moderate NPDR. Details of the retinal microvasculature were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 56 publications
9
145
1
1
Order By: Relevance
“…Retinal photographs that utilize adaptive optics technology to compensate for wavefront aberrations in individual eyes allow imaging with a theoretical resolution limit down to 2 μm and have greatly expanded the ability to visualize the retina on a cellular level. Adaptive optics studies demonstrate changes in the cone photoreceptor mosaic in the diabetic eye (42) and allow visualization of early vascular changes that cannot be identified on standard photographs (43).…”
Section: Evaluating the Diabetic Retinamentioning
confidence: 99%
“…Retinal photographs that utilize adaptive optics technology to compensate for wavefront aberrations in individual eyes allow imaging with a theoretical resolution limit down to 2 μm and have greatly expanded the ability to visualize the retina on a cellular level. Adaptive optics studies demonstrate changes in the cone photoreceptor mosaic in the diabetic eye (42) and allow visualization of early vascular changes that cannot be identified on standard photographs (43).…”
Section: Evaluating the Diabetic Retinamentioning
confidence: 99%
“…In the upper right corner individual nerve fiber bundles can be observed while in the lower left corner the capillary network of the inner plexiform layer can be observed. In the SLO image residual backscattering signal from the photoreceptor layer can be observed which leads to the typical appearance (bright central core that is surrounded by a dark area on both sides) of the large vessel in confocal SLO images [50]. The central core originates from the strong backscattering of the erythrocytes and the top vessel wall while the dark bands originate from the shadow caused by the erythrocytes that is visible in layers below the vessel.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with mild to moderate non-proliferative diabetic retinopathy (Burns et al 2014) used offset pupil AOSLO and found significant vessel remodeling and revealed microvascular abnormalities with exquisite detail. Quantitatively, they found larger capillary diameters than normal (8.2 +/- 1.1 vs. 6.1 +/- 0.75 micrometers) around the foveal avascular zone.…”
Section: 0 How Is Aoslo Being Used Clinically?mentioning
confidence: 99%